SPECIAL MONTH FOR SPECIAL NEEDS CHILDREN - Maritska, Ziske; Arroyantri Prananjaya, Bintang; Parisa, Nita (International Journal of Islamic and Complementary Medicine, 2022)
Down Syndrome is one of the most commonly found genetic conditions, a chromosomal abnormality that is. It is caused by an extra chromosome 21 in their body. The extra chromosome itself can be a total chromosome 21, or just part of it. Whatever the form is, it leads to distinct physical features along with associated medical conditions. One of the symptoms of people with Down Syndrome is the cognitive problem where all of them would have various levels of intelligence, making the learning and comprehension process challenging. For Muslims all around the world, Ramadhan is the one special month of the year where everyone would fast. Learning about Ramadhan and conducting fasting during Ramadhan could be challenging for children with Down Syndrome. There is no known absolute contraindication for them to fast, but several comorbidities related to the condition might hinder them from doing fasting.